2020
DOI: 10.2147/idr.s236898
|View full text |Cite
|
Sign up to set email alerts
|

<p>Trends in Molecular Markers Associated with Resistance to Sulfadoxine-Pyrimethamine (SP) Among <em>Plasmodium falciparum</em> Isolates on Bioko Island, Equatorial Guinea: 2011–2017</p>

Abstract: Antimalarial drug resistance is one of the major challenges in global efforts to control and eliminate malaria. In 2006, sulfadoxine-pyrimethamine (SP) replaced with artemisinin-based combination therapy (ACT) on Bioko Island, Equatorial Guinea, in response to increasing SP resistance, which is associated with mutations in the dihydrofolate reductase (Pfdhfr) and dihydropteroate synthase (Pfdhps) genes. Patients and Methods: To evaluate the trend of molecular markers associated with SP resistance on Bioko Isla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
2
3
0
Order By: Relevance
“…It can be seen that the partially resistant (IRNG) and fully resistant (IRNGE) haplotypes have been progressively increasing since 1999, reaching their peak in 2019, whereas the super-resistant (IRNGEG) have always had a low trend over time, never exceeding 2% and not being found in 2019. The data obtained are consistent with previous studies with samples from the island of Bioko, where the partially and fully resistant types were the most common and the frequency of the super-resistant type was very low [ 57 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It can be seen that the partially resistant (IRNG) and fully resistant (IRNGE) haplotypes have been progressively increasing since 1999, reaching their peak in 2019, whereas the super-resistant (IRNGEG) have always had a low trend over time, never exceeding 2% and not being found in 2019. The data obtained are consistent with previous studies with samples from the island of Bioko, where the partially and fully resistant types were the most common and the frequency of the super-resistant type was very low [ 57 ].…”
Section: Discussionsupporting
confidence: 91%
“…Current WHO recommendations suggest that SP-IPTp should be discontinued if the frequency of 540E exceeds 50% and that of 581G exceeds 10% [ 57 ]. Based on current evidence, IPTp and IPTi remain effective in preventing the adverse consequences of malaria on maternal, foetal and infant outcomes in Equatorial Guinea.…”
Section: Discussionmentioning
confidence: 99%
“…It can be seen that the partially resistant (IRNG) and fully resistant (IRNGE) haplotypes have been progressively increasing since 1999, reaching their peak in 2019, whereas the super-resistant ones (IRNGEG) have always had a low trend over time, never exceeding 2% and not being found in 2019. The data obtained are consistent with previous studies with samples from the island of Bioko, where the partially and fully resistant types were the most common and the frequency of the super-resistant type was very low [57].…”
Section: Discussionsupporting
confidence: 91%
“…Although resistance-related haplotypes to SP exhibit an upward trend, it has been observed that mutations at positions 540E (36.6%) and 581G (1.4%) are not su ciently high to jeopardise the use of SP in IPT. Current WHO recommendations suggest that SP-IPTp should be discontinued if the frequency of 540E exceeds 50% and that of 581G exceeds 10% [57]. Based on current evidence, IPTp and IPTi remain effective in preventing the adverse consequences of malaria on maternal, foetal and infant outcomes in Equatorial Guinea.…”
Section: Discussionmentioning
confidence: 99%
“…At present, severe malaria is treated with drugs such as chloroquine, sulfadoxine-pyrimethamine, quinine, and artemisinin and its derivatives (artemether, artesunate). However, two of the safest and cost-effective drugs, chloroquine and sulfadoxine-pyrimethamine, have lost their efficacy in most malaria-endemic countries because of drug resistance (Lin et al, 2020;Mharakurwa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%